The Use of Genially Assisted Problem Based Learning (PBL) Methods in Class VIII Students' Learning to Write Explanation Texts - Dede Abdurrokhman; Dede Hamimudin; Yeni Rostikawati (JLER (Journal of Language Education Research), 2023)
Study This motivated by difficulties student in write text explanation, fine in determine structure, content and language text explanation. Most student Still Not yet understand in write text explanation. From the average count the can concluded that post test Skills write text explanation after use method learning problem-based learning (PBL) assisted genially in learning write text explanation to students Class VIII is influential. Skills write text Explanation is also possible achieve the specified KKM For eye Indonesian language lessons at SMP Negeri 6 Cikalongkulon is 70 students reached an average of 76.32. because that, post test Skills write text explanation seen capable reach mark from the KKM determined by the school the. Can seen when the process occurs less learning so active inside class. In the end when create or write work text explanation so found use less EYD so right. Use sign dots and commas are not used at all in the writing of these students in writing explanatory texts. It will be seen that the results of students' writing in writing explanatory texts are quite good from some of the works found in this study.